Pengolahan kue bolu Daun Kelor (Moringa oleifera) dan sate lilit ikan Patin (Pangasius djambal) di Desa Kuok Kecamatan Kuok Kabupaten Kampar - Trisla Warningsih; Kusai Kusai; Andarini Diharmi; Tince Sofyani; Rindi Metalisa; Muhammad Arief; Tessha Fitriani; M. Faiz Akhimuddin; Silfi Zuhriani; Herawati Br Ginting; Marifa Indar Wara Gandini; Siti Aminah; Yuni Suseno; Deando Hentun Gultom; Feby Dwi Anisha Putri (Unri Conference Series: Community Engagement, 2022)
This community service program aims to innovate in the manufacture of products made from Moringa leaves (Moringa oleifera) and catfish (Pangasius spl) in Kuok Village. The method applied in this activity is the socialization and trial of making catfish satay wraps and Moringa leaf sponge cake. The target communities in this activity are women in Kuok Village who are members of the Kuok Village PKK and the community around the Lontiok Kandil Kemilau Emas House. This activity resulted in a new perspective in the Kuok Village community in empowering women to support the household economy by innovating and participating in trials of making catfish satay wraps and Moringa leaf sponge cake.